Asthma control during and after cessation of regular beta 2-agonist treatment. - Wahedna, I; Wong, C; Wisniewski, A; Pavord, I; Tattersfield, A (1993)
It has been suggested that regular treatment with high doses of beta 2-agonists might result in poorer control of asthma and increased bronchial responsiveness. We have examined change in FEV1 (delta FEV1), bronchial reactivity, peak expiratory flow (PEF), and symptoms during and after 3 wk of regular treatment with a relatively low dose of albuterol and broxaterol, a new beta 2-agonist. Eleven subjects 18 to 50 yr of age with mild asthma inhaled albuterol (200 micrograms), broxaterol (400 micrograms), or placebo three times a day for 3 wk with a 2- to 4-wk run-in/washout period between treatments. Ipratropium bromide was allowed for symptomatic relief. The PD20 (dose of histamine causing a 20% fall in FEV1) was measured before and 11, 35, and 59 h after cessation of treatment and a bronchodilator dose-response study before and 83 h after cessation of treatment. Change from baseline after albuterol and broxaterol are compared with change after placebo. Diurnal change in PEF (amplitude % mean) increased during treatment with albuterol by 6.5% (95% CI, 1.7-12.3; p < 0.02) mainly because of a fall in morning PEF. Cessation of treatment with both beta 2-agonists was associated with a fall in FEV1 and PD20 compared with placebo.(ABSTRACT TRUNCATED AT 250 WORDS)